Corporate Social Responsibility dalam Perspektif Good Governance (Studi pada Kantor BRI Kantor Cabang Malang Kawi) - Pratiwi Nurul Khoiriyah (Jurnal Administrasi Publik, 2014)
Abstract: Corporate Social Responsibility in Good Governance Perspective (Study on the Bank Rakyat Indonesia Kawi Malang). This study aims to analyze Corporate Social Responsibility conducted by BRI Kawi Malang in the perspective of good governance as well as the supporting factors and inhibiting factors affecting the program. This study used qualitative research methods with a descriptive approach. The model of data analysis used is the model interactive of Miles and Huberman. This research results show that Corporate Social Responsibility conducted by BRI Kawi Malang focuses on social activities especially education. BRI Kawi Malang effort applying Corporate Social Responsibility in realizing good governance conducted through application participation principle, transparency, accountability, and responsibility. However, there are supporting factors and inhibiting factors affecting the application Corporate Social Responsibility on the banks. Suggestions that can be given related research result are a chance to community for proposing proposals of Corporate Social Responsibility and improvements of laboratory facilities in mini banks. Keywords : Corporate Social Responsibility, good governance, Bank Rakyat Indonesia Â  Abstrak: Corporate Social Responsibility dalam Perspektif Good Governance (Studi pada Kantor BRI Kanca Malang Kawi). Penelitian ini bertujuan untuk menganalisis Corporate Social Responsibility yang dilakukan BRI Kanca Malang Kawi dalam perspektif good governance serta faktor pendukung dan faktor penghambat yang mempengaruhi program tersebut. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Model analisis data yang digunakan adalah model analisis interaktif menurut Miles dan Huberman. Hasil penelitian menunjukkan bahwa Corporate Social Responsibility yang dilakukan BRI Kanca Malang Kawi menitikberatkan pada kegiatan sosial khususnya bidang pendidikan. Upaya BRI Kanca Malang Kawi menerapkan Corporate Social Responsibility dalam mewujudkan good governance dilakukan melalui penerapan prinsip partisipasi, transparansi, akuntabilitas, dan responsibilitas. Namun terdapat faktor pendukung dan penghambat yang mempengaruhi penerapan Corporate Social Responsibility pada BRI Kanca Malang Kawi. Saran yang dapat diberikan terkait hasil penelitian adalah dengan memberikan kesempatan kepada pihak swasta untuk mengajukan proposal Corporate Social Responsibility dan meningkatkan sarana hingga fasilitas penunjang laboratorium mini bank. Â  Kata Kunci: Corporate Social Responsibility, good governance, Bank Rakyat Indonesia